Ways of coping with stress, level of anxiety and level of burnout of medical staff during the Covid-19 pandemic - Adamczyk, Katarzyna (2024)
The doctoral thesis attempted to examine the relationship between the specificity of the work environment of health care workers during the Covid-19 pandemic and the occurrence of signs of burnout syndrome and anxiety. Attention was paid to factors predisposing to the development of burnout among employees in the context of the Covid-19 pandemic. The research group consisted of professionally active doctors and nurses, psychologists, physiotherapists, and medical caregivers. The study was conducted at the University Hospital in Krakow. The research was carried out using standardized research tools that assessed the level of burnout, styles of coping with stress and anxiety. The adopted theoretical framework corresponded to selected concepts of burnout, ways of coping with stress and the concept of anxiety as a state and trait. The obtained research results showed what ways of coping with stress were chosen by different professional groups of medical workers during the Covid-19 pandemic. This study attempts to find differences in the picture of burnout between doctors, nurses, and other medical professions. During the crisis caused by the Covid-19 pandemic, doctors and nurses subjectively assessed themselves as more professionally burnt out. The conducted research supplements the knowledge regarding the emotional burdens of health care workers and their psychosoci
Keywords: occupational burnout; psychophysical exhaustion; occupational stress; coping; coping strategies; anxiety